(untitled) (Sains Humanika, 2020)
Distributed leadership is a leadership theory that emphasis on cooperation among leaders. It is practiced in schools, an institution that not only educates pupils but now serves as a professional learning community for school leaders and teachers. This study aims to investigate the influence of distributed leadership towards a professional learning community among the school leaders in Johor, Malaysia. This study uses quantitative approach and involves 27 secondary schools from six districts in Johor. Sample study is a school leader consisting of principal, senior assistant, senior teachers and head committee subjects. The respondent is a total of 358 people. Data collected using the Perception of Distributed Leadership Practices (PDLP) questionnaire by Hairon and Goh, (2015) and Professional Learning Communities Assessment-Revised (PLCA-R) by Olivier et al., (2010). Data was analyzed using SPSS Amos software version 26. Studies find all the common shared decision making have a significant influence on all the dimensions of professional learning communities. Bounded empowerment practices are found to influence only one of the dimensions of professional learning communities, namely learning and application collectively. It is hoped that this study would enhance the leadership practices of the distributive of the school leaders in the professional learning community.